PERUBAHAN NILAI TUKAR UANG MENURUT PERSPEKTIF EKONOMI ISLAM - Leni Saleh (Institut Agama Islam Negeri Kendari, 2016)
Abstract Changes in the exchange rate is an important issue because the exchange rate is always changing and is not permanent. In economic theory, reduced and increased the amount of money for a person if pursued in a fair, because money can not develop with itself without any work done. In the Islamic economic system of currency exchange is still controversy in the changes resulting from the exchange rate outstanding. As well as with the existing implications of changes in the excange rate, which is an important Islamic economic discourse, so it should be in revisit the principles according to Islamic economic perspective. Based on the results of studies describing the discussion of this literature study/library, showed that : (1) exchange rate in Islamic economics is part of a transaction that mubah or allowed. Currency exchange either from the same country as well as an other countries must meet the requirements that exist in Islamic economics, (2) the implications of changes in currency exchange rates not only impact on the level of domestic goods but also affecting the price of the currency a country, so that deflation and inflation can not be avoided. The implication of changes in the exchange rate of the most looked for our nation that the currency crisis that hit Indonesia and other countries in Asia. The economy collapsed due to changing currency values, resulting in rising prices of goods,both domestic and non domestic high, and (3) in the economic system of Islam, the concept of time value of money is not there. There is the concept of economic value of time. The future which has a value of economic, not money that has economic value. That if the time to good use, efficient and efectif, because increasing and decreasing the value of money if pursued with those efforts. Keywords: Change, exchange rate, and Islamic economic.